2021
DOI: 10.1371/journal.pone.0251593
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 transmission in students of public schools of Catalonia (Spain) after a month of reopening

Abstract: Introduction SARS-CoV-2 transmission within schools and its contribution to community transmission are still a matter of debate. Methods A retrospective cohort study in all public schools in Catalonia was conducted using publicly available data assessing the association between the number of reported SARS-CoV-2 cases among students and staff in weeks 1–2 (Sept 14-27th, 2020) of the academic year with school SARS-CoV-2 incidence among students in weeks 4–5. A multilevel Poisson regression model adjusted for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Our study considered propagation inside bubble groups between 15 and 30 individuals. The extension to larger groups like whole schools with more than 500 individuals, may give rise to fictitious higher propagation because the high probability of simultaneous appearance of independent index cases, especially during high incidences outside the schools [ 35 ]. In general, the values of R*, smaller than 1, obtained here, were related with low propagation [ 19 ] and confirmed that in Catalonia, return to face-to-face activities did not appear to trigger transmission or outbreaks, with schools facilitating epidemiological surveillance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study considered propagation inside bubble groups between 15 and 30 individuals. The extension to larger groups like whole schools with more than 500 individuals, may give rise to fictitious higher propagation because the high probability of simultaneous appearance of independent index cases, especially during high incidences outside the schools [ 35 ]. In general, the values of R*, smaller than 1, obtained here, were related with low propagation [ 19 ] and confirmed that in Catalonia, return to face-to-face activities did not appear to trigger transmission or outbreaks, with schools facilitating epidemiological surveillance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of active SARS-CoV-2 infections detected by the project was low considering the overall prevalence and incidence from Catalonia during the same period [ 3 , 20 , 30 , 31 ]. This suggests that public health strategies such as testing of symptomatic individuals and contact tracing efforts were effective at identifying an active infection at school, even the asymptomatic population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering detected and self-reported infections in our longitudinal study we found a low incidence of COVID-19 infections, consistent with other studies that have very similar results to ours [ 28 , 32 34 ]. Also, there are studies suggesting that higher community incidence, diagnostic issues [ 30 ], demographic and economic aspects are determinants in the variation of different rates detected, as showed in these studies [ 16 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, education has rotated between remote and in-person learning. However, even when in-person learning was offered quarantine and isolation periods for COVID-19 infections and exposures affected as many as 20% of students during pandemic waves in both Spain and China ( 3 , 88 , 89 ). Shifts between modes of learning have led to negative social, emotional, educational, and physical consequences not only through reduced physical presence in school buildings, but also through loss of essential services for children provided by schools ( 90 92 ).…”
Section: Impact Of School Closures Remote or Hybrid Learning And Quarantine Periodsmentioning
confidence: 99%